1987
DOI: 10.1161/01.hyp.9.6.582
|View full text |Cite
|
Sign up to set email alerts
|

Absence of hypertension despite chronic marked elevations in plasma norepinephrine in conscious dogs.

Abstract: SUMMARY To better define the mechanisms of blood pressure control in states of catecholamine excess, we infused norepinephrine for 28 days using subcutaneously implanted osmotic pumps in dogs previously instrumented for monitoring left ventricular dynamics and cardiac output. Plasma norepinephrine rose from 238 ± 27 to 4346 ± 952 pg/ml at 21 days, while epinephrine and dopamine levels did not change. Heart rate fell from 85 ± 4 to 63 ± 6 beats/min, while arterial pressure was unchanged from baseline. Total per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…However, an excellent agreement has been reported between the radioenzymatic method and high-performance liquid chromatography, which measures NE specifically (31). In a previous, similar study (32) plasma levels of catecholamine were measured with high performance liquid chromatography as well as by the radioenzymatic method, and the plasma levels of NE were demonstrated to be similar to ours.…”
Section: Discussionsupporting
confidence: 84%
“…However, an excellent agreement has been reported between the radioenzymatic method and high-performance liquid chromatography, which measures NE specifically (31). In a previous, similar study (32) plasma levels of catecholamine were measured with high performance liquid chromatography as well as by the radioenzymatic method, and the plasma levels of NE were demonstrated to be similar to ours.…”
Section: Discussionsupporting
confidence: 84%
“…In 10 animals 2 ml saline was placed in the pump, while in 16 animals NE was placed in the pump to infuse at a rate of 0.5 gg/kg per min over a 2-wk period. A second pump was implanted 10 d to 2 wk after the first pump so that the duration ofthe chronically high NE levels was 3-4 wk (4). Plasma NE samples were drawn from the chronically implanted aortic catheter and levels were assayed weekly in animals with NE pumps to assure sustained high levels of NE.…”
Section: Methodsmentioning
confidence: 99%
“…a 1 -Adrenergic Receptor-Mediated Hypertrophy in Animal Models. Early studies in mice, cats, and dogs showed that long-term catecholamine infusion in various species and at doses that do not increase blood pressure produces cardiac hypertrophy in vivo, which is "physiological," in that cardiac function is normal or improved and there is no fibrosis (Laks et al, 1973;King et al, 1987;Marino et al, 1991;Patel et al, 1991;Stewart et al, 1992;Vecchione et al, 2002). Whereas these studies suggest clearly that activation of ARs induces cardiac hypertrophy directly, which was debated at the time, the lack of subtype-specific AR pharmacologic agents limits mechanistic insight.…”
Section: A a 1 -Adrenergic Receptors Activate Physiologic Or Adaptivmentioning
confidence: 99%